A new EKF-based algorithm for flux estimation in induction machines - Salvatore, L.; Stasi, S.; Tarchioni, L. (IEEE transactions on industrial electronics (1982), 1993)
A reduced-order algorithm for estimating the rotor flux components of induction motors with schemes such as field-oriented control is described. The algorithm is based on the extended Kalman filter (EKF) theory and estimates the desired quantities online using only measurements of the stator voltages and currents and the rotor speed. The online adaptation of the inverse rotor time constant makes it possible to obtain very accurate estimates of rotor flux components, in spite of temperature and magnetic saturation effects. The algorithm order reduction decreases the computational complexity and makes the proposed estimator superior to others based on EKF theory.< >